Mitral flow propagation velocity in non-sedated healthy cats - A.C. Silva; R.A.L. Muzzi; G. Oberlender; L.A.L. Muzzi; M.R. Coelho; R.B. Nogueira (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2014)
Mitral flow propagation velocity (Vp) is an index used to evaluate the left ventricular diastolic function. Its influence on human and small animal cardiopathies has been studied; however there are few reports evaluating this variable in domestic felines. In addition, there is a lack of studies in non-sedated healthy cats. Therefore, the purpose of this study was to establish values for Vp and its correlation with other echocardiographic indexes in non-sedated healthy cats in order to provide new perspectives related to diastolic function in this species. Twenty-six clinically healthy cats were submitted to echocardiography to assess the animals' cardiac conditions. Variables such as age, heart rate (HR), body surface area (BSA), initial (E mitral) and late (A mitral) ventricular filling waves, isovolumic relaxation time (IVRT) and E/IVRT relation were correlated to Vp. No proven relation between any of these variables and Vp was observed in this present study, except for HR and BSA. In the variability analysis, higher values were verified for inter-observer analysis. This study concludes that Vp proved to be an useful index for estimating left ventricular relaxation in non-sedated healthy domestic cats and provides reference ranges for this variable.